Bioautography and GC-MS of the antidermatophytic components of the methanol leaf extract of Musa paradisiaca Linn - Asuquo, Ememobong; Akpanenang, Edet; Udobi, Chinwezu; Onele, Ugochukwu; Nwosu, Chibuzor (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: The search for new agents from medicinal plants is on the increase because of the development of resistance to available drugs. Methods: The methanol leaf extract of Musa paradisiaca Linn was investigated to isolate its antidermatophytic components. The extract was fractionated to pool the active compounds into the polar solvent. The functional groups present in the extract were detected by FTIR, while chemical components of the extract were separated by TLC methods before determining the activity of the separated components by bioautography. The components were isolated and tested for their individual activity against the test dermatophytes. Results: Infrared spectra indicated the presence of organic compounds of the phenolic group. All the test organisms had varying degrees of susceptibility on the bioautoghrahy, with M. audouinii being more susceptible. GC-MS analysis of the components indicated the presence of oxirane tridecyl, 12-methyl-E, E-2, 13 octadecadien-1-ol, cis-7, cis-11-Hexadecadien-1-yl acetate, n-Hexadecanoic acid, cis-11-Hexadecenal, 2-Hexadecanol and butylated hydroxytoluene which are known to possess antifungal properties. Conclusion: The leaf of M. paradisiaca is confirmed to possess antidermatophtytic potentials which can be exploited to produce leads for the development of novel antifungal agents.